Representation of Patriarchal Culture in the Legong Lanang Dance in Denpasar City - Eva Riyanti (Melayu Arts and Performance Journal, 2026)
Legong Lanang is a Balinese performing art that has undergone significant transformation alongside social and cultural changes within Balinese society. Originally performed by male dancers, it later became predominantly associated with female performers before eventually being revived as a male dance performance. This transformation demonstrates that the performance is not merely an aesthetic expression but also reflects power relations, gender construction, and patriarchal culture embedded within society. Although previous studies have examined Legong dance from historical, aesthetic, and choreographic perspectives, limited attention has been given to the representation of patriarchal culture in Legong Lanang. This study aims to analyze how patriarchal culture is represented through the performance elements of Legong Lanang in Denpasar City. Employing a qualitative approach within the framework of cultural studies, data were collected through participant observation, in-depth interviews, document analysis, and literature review involving dancers, artists, cultural practitioners, and supporting documents. The data were analyzed using descriptive-interpretative techniques informed by theories of representation, semiotics, aesthetics, and hegemony to reveal the construction of meaning within the performance. The findings indicate that patriarchal representation is constructed through choreographic structure, characterization, movement vocabulary, costume and make-up, musical accompaniment, and the symbolic dominance of male performers within the performance arena. These elements collectively construct a cultural system that reproduces while simultaneously negotiating masculine identity within Balinese performing arts. This study contributes to the development of performing arts and cultural studies by explaining the relationship between artistic practice and socio-cultural construction. The novelty of this research lies in its analysis of Legong Lanang as a cultural representation through which patriarchal values are negotiated amid contemporary social transformation in Balinese society.